Integrin beta4 mAb inhibited apoptosis induced by deprivation of growth factors in vascular endothelial cells - ZHAO Ke-wen; ZHAO Qi-tao; ZHANG Shang-li; MIAO Jun-ying (Acta Pharmacologica Sinica; Vol 25, No 6 (June 2004): Acta Pharmacologica Sinica, 2016)
AIM: To understand the mechanism by which anti-beta4 integrin monoclonal antibody (mAb) inhibits apoptosis of vascular endothelial cells (VEC). METHODS: Viability was determined by counting the cells that attached to dishes after treatments. DNA fragmentation was analyzed by agarose gel electrophoresis and fluorescence microscopy. The intracellular content of cAMP was measured by radioimmunoassay (RIA). The levels of p53 and Ras expressions were analyzed by fluorescence microscopy combined with immunofluorescence under laser scanning confocal microscopy. RESULTS: After the cells were deprived of fibroblast growth factor (FGF) and serum were exposed to the mAb 5 mg/L for 24 h, the detachment and DNA fragmentation of these cells were suppressed. When cells were deprived of FGF and serum, the intracellular cAMP level and Ras protein content decreased (P